2003
DOI: 10.1128/iai.71.6.3551-3562.2003
|View full text |Cite
|
Sign up to set email alerts
|

Catalases of Aspergillus fumigatus

Abstract: Upon infection of a host, the pathogenic fungus Aspergillus fumigatus is attacked by the reactive oxygen species produced by phagocytic cells. Detoxification of hydrogen peroxide by catalases was proposed as a way to overcome this host response. A. fumigatus produces three active catalases; one is produced by conidia, and two are produced by mycelia. The mycelial catalase Cat1p was studied previously. Here we characterized the two other catalases, their genes, and the phenotypes of gene-disrupted mutants. CatA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
174
0
10

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(191 citation statements)
references
References 45 publications
5
174
0
10
Order By: Relevance
“…Differential expression levels of the other proteins identified in our study have not been reported previously. Catalase-peroxidase and isocitrate lyase have been reported to be related to pathogenicity in other fungi (Lorenz & Fink, 2001;Paris et al, 2003). Catalaseperoxidase shows bifunctional activity of both catalase and peroxidase to transform intracellular reactive oxygen species into harmless products in Aspergillus fumigatus and Aspergillus nidulans (Kawasaki & Aguirre, 2001; Paris et al, Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Differential expression levels of the other proteins identified in our study have not been reported previously. Catalase-peroxidase and isocitrate lyase have been reported to be related to pathogenicity in other fungi (Lorenz & Fink, 2001;Paris et al, 2003). Catalaseperoxidase shows bifunctional activity of both catalase and peroxidase to transform intracellular reactive oxygen species into harmless products in Aspergillus fumigatus and Aspergillus nidulans (Kawasaki & Aguirre, 2001; Paris et al, Table 2 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Dihydropteroate synthase (Afu3g07630) has been associated with drug resistance in Saccharomyces cerevisiae and has been shown to be derived from a polycistronic gene also responsible for the production of two other functional proteins [16]. Catalase 1 (Afu3g02270) involved in oxidative stress and identified here as three separate protein spots has been implicated in A. fumigatus pathogenicity [17]. Almost 44% (22/50) of all proteins identified were derived from intron-containing genes.…”
Section: Aspergillus Fumigatus Proteome Analysismentioning
confidence: 99%
“…Further, we found that topical application of PX-12 was sufficient to restrict fungal growth in vivo, thereby indicating that this or similar compounds that target the thioredoxin pathway can block fungal thioredoxins and inhibit the predominant antioxidant defense utilized by these pathogens during infection. Figure 10 also illustrates that A. fumigatus produces 3 superoxide dismutases that catalyze the conversion of superoxide to H 2 O 2 (37,38). SOD1 and SOD3 are both cytoplasmic, whereas SOD2 is restricted to the mitochondrial membrane (37).…”
Section: Figure 10mentioning
confidence: 99%
“…For example, A. fumigatus superoxide dismutases (SOD1/2/3) convert superoxide to the less-reactive hydrogen peroxide (37), whereas A. fumigatus catalases (CatA/1/2) convert hydrogen peroxide to H 2 O (38). In addition to ROS-catabolizing enzymes, filamentous fungi including A. fumigatus produce secondary metabolites such as gliotoxin and fumagillin, which inhibit NOX and are controlled by the master transcriptional regulator protein LaeA (39)(40)(41).…”
Section: Figurementioning
confidence: 99%